PENGARUH PEMAKAIAN LENSA BLUE CUT TERHADAP KENYAMANAN PEMAKAIAN KACAMATA DI OPTIK JAYA PASAMAN BARAT - Suryanta, D.I (Ensiklopedia Sosial Review, 2020)
Impaired vision makes someone have to use visual aids so that vision becomes clear. Various ways are done by people, such as using glasses, contact lenses and even lasik surgery. The addition of blue cut lenses to glasses is generally used to help human vision against eye weakness due to nearsightedness or other visual reasons and protect the eyes from UV rays. The research objectives were (1) to determine the effect of using blue cut lenses on the comfort of wearing glasses in West Pasaman optics. (2) To determine the advantages of blue cut lenses on eye health for eyeglass users at Optic Zal Pondok Padang. The type of research used is descriptive quantitative, the research process was carried out by interviewing by distributing questionnaires, this study aims to obtain an overview of the effect of using blue cut lenses on the comfort of wearing glasses in West Pasaman Jaya optics. The population in this study were all patients at an early age who experienced refractive errors in the study, amounting to 30 people. Considering the population under study was less than 100 people, the sample in this study were all consumers of Jaya Pasaman Barat optics totaling 30 people. The study was conducted on early age patients at Optik Jaya Pasaman Barat. The results showed that the respondents that 61.7% of the respondents know the effect of wearing blue cut lenses on the comfort of wearing glasses, this is because they do not know the impact of UV rays on eye health and 60.1% of blue cut lenses have the advantage of maintaining eye health. Based on the results of this study, it was concluded that as much as 61.7% response to know the effect of using blue cut lenses on the comfort of wearing glasses in West Pasaman Jaya optics. This is due to the lack of knowledge of respondents about the impact of blue light on eye health. Based on the results of the research the effect of using blue cut lenses on the comfort of wearing glasses in West Pasaman optics, the results showed that as many as 60.7% of respondents knew the advantages of blue cut lenses and it was suggested to the public that when dealing directly with patients, they must wear anti-radiation lenses that are familiar with blueray lenses.